AGROECOLOGY DYNAMICS IN SUSTAINABLE AGRICULTURE APODI-RN - Jeronimo, Carlos Enrique de Medeiros; Araújo, Ana Beatriz Alves de; Benjamim, Érika (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The Access policies the ability to organize collectively and inclusion in markets are continuously barriers to the segment of the family farm. Challenging these problems, a group of women in agrarian reform settlement Mulunguzinho of Mossoró (RN), initiated in 1999 a procedure for agricultural production based on principles of agroecology, and so forerunner in the region, sought to integrate its production to solidary consumption. This action, which was guided and supported by NGOs, pocketed reliability of the company about to expand and today we find this in ten municipalities in Rio Grande do Norte by Network Xique Xique. The methodology consisted of applying questionnaires in 169 production facilities in 21 rural communities in order to identify skills and knowledge introduced by farmers related to Network Chique Chique. The main variables analyzed were: the use of chemical inputs and performs agroecological practices. It was found, therefore, that Apodi experience configuring a diversified family farming Network Xique Xique and has a high potential for expansion of agroecological practices. However, its production structures are weak due to absence of technical assistance. This necessitates the action policies that help farmers to overcome challenges, because even with limitations that experience already contributes to the transition from traditional to agroecosystems.